Micropillar compression of single crystal tungsten carbide, Part 1: Temperature and orientation dependence of deformation behaviour. (January 2022) - Jones, Helen; Tong, Vivian; Ramachandramoorthy, Rajaprakash; Mingard, Ken; Michler, Johann; Gee, Mark
Abstract: Tungsten carbide cobalt hardmetals are commonly used as cutting tools subject to high operation temperature and pressures, where the mechanical performance of the tungsten carbide phase affects the wear and lifetime of the material. In this study, the mechanical behaviour of the isolated tungsten carbide (WC) phase was investigated using single crystal micropillar compression. Micropillars in two crystal orientations, 1-5 μm in diameter, were fabricated using focused ion beam (FIB) machining and subsequently compressed between room temperature and 600 °C. The activated plastic deformation mechanisms were strongly anisotropic and weakly temperature dependent. The flow stresses of basal-oriented pillars were about three times higher than the prismatic pillars, and pillars of both orientations soften slightly with increasing temperature. The basal pillars tended to deform by either unstable cracking or unstable yield, whereas the prismatic pillars deformed by slip-mediated cracking. However, the active deformation mechanisms were also sensitive to pillar size and shape. Slip trace analysis of the deformed pillars showed that 10 1 ¯ 0 prismatic planes were the dominant slip plane in WC. Basal slip was also activated as a secondary slip system at high temperatures. Graphical abstract: Image 1 Highlights: Single crystal WC micropillar compression from room temperature to 600 °C. Basal directions 3 × stronger than prismatic directions in compression. Micropillar shape artefacts affect cracking versus yielding behaviour. Primary slip planes are 10 1 ¯ 0 from room temperature to 600 °C. Secondary slip on (0001) plane activated at 600 °C.